2014
DOI: 10.1111/jce.12379
|View full text |Cite
|
Sign up to set email alerts
|

Eplerenone‐Mediated Regression of Electrical Activation Delays and Myocardial Fibrosis in Heart Failure

Abstract: MR antagonism regresses rapid pacing-induced electrical delays, inflammatory cytokine gene activation, and fibrosis in heart failure. Ventricular arrhythmia vulnerability in heart failure is correlated with extent of fibrosis and electrical activation delays during premature excitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…43 A high-salt diet may stimulate oxidative stress, which then promotes activation of the MR. 44 Thus, there may be a synergism between activation of the MR and oxidative stress, although the mechanisms for this are yet to be fully elucidated. 5 Crosstalk and interactions between the MR and the angiotensin receptor 1 have also been proposed to contribute to end-organ damage in both the heart and kidneys.…”
Section: February 2015mentioning
confidence: 99%
“…43 A high-salt diet may stimulate oxidative stress, which then promotes activation of the MR. 44 Thus, there may be a synergism between activation of the MR and oxidative stress, although the mechanisms for this are yet to be fully elucidated. 5 Crosstalk and interactions between the MR and the angiotensin receptor 1 have also been proposed to contribute to end-organ damage in both the heart and kidneys.…”
Section: February 2015mentioning
confidence: 99%
“…It has been described that the connective tissue around the lead tip forms as part of a foreign body response and after microinjury to the local tissues with subsequent organization of the deposited thrombus via a macrophage‐dominated phase that eventually creates a fibrous capsule. This subsequent fibrosis concludes the adverse electrical remodeling as cardiomyocytes are nonregenerative cells and the “status quo ante” cannot be regained . Steroids and their well‐documented antiinflammatory properties clearly mitigate these undesired events and lead to earlier stabilization …”
Section: Discussionmentioning
confidence: 99%
“…This subsequent fibrosis concludes the adverse electrical remodeling as cardiomyocytes are nonregenerative cells and the "status quo ante" cannot be regained. 15 Steroids and their welldocumented antiinflammatory properties clearly mitigate these undesired events and lead to earlier stabilization. 16 The current studies examined via histopathology 12-week-old implants of LVCV leads in dogs.…”
Section: Histomorphological Effect Of Se Around Pacing Electrodesmentioning
confidence: 99%
“…Mineralocorticoid receptor antagonists (MRA), such as spironolactone, have been shown, in animal models and in the clinical setting, to slow the rate of development of cardiac fibrosis and remodeling after cardiac injury (Baldo et al., 2011; Brilla, Matsubara, & Weber, 1993a; Lacolley et al., 2001; Tanaka‐Esposito, Varahan, Jeyaraj, Lu, & Stambler, 2014), which is thought to be both dependent and independent of the actions of angiotensin II (Briet & Schiffrin, 2010; Colussi, Catena, & Sechi, 2012; Messaoudi, Azibani, Delcayre, & Jaisser, 2012; Nagata, 2008). While a number of studies have explored the potential renal protective effects of spironolactone (Barrera‐Chimal et al., 2012; Han et al., 2006; Nielsen et al., 2002; Ortiz, Graciano, Mullins, & Mitchell, 2007), very few studies have been performed in hypertensive animal models and these have reported variable results (Ashek et al., 2012; Baumann et al., 2007; Klanke et al., 2008).…”
Section: Introductionmentioning
confidence: 99%